Peptain-1 blocks ischemia/reperfusion-induced retinal capillary degeneration in mice - Nam, Mi-Hyun; Dhillon, Armaan; Nahomi, Rooban B.; Carrillo, Noelle L.; Hougen, Clarinda S.; Nagaraj, Ram H. (Frontiers in Cellular Neuroscience, 2024)
Introduction Neurovascular degeneration results in vascular dysfunction, leakage, ischemia, and structural changes that can lead to significant visual impairment. We previously showed the protective effects of peptain-1, a 20 amino acid peptide derived from the αB-crystallin core domain, on retinal ganglion cells in two animal models of glaucoma. Here, we evaluated the ability of peptain-1 to block apoptosis of human retinal endothelial cells (HRECs) in vitro and retinal capillary degeneration in mice subjected to retinal ischemia/reperfusion (I/R) injury. Methods HRECs were treated with either peptain-1 or scrambled peptides (200 μg/mL) for 3 h and a combination of proinflammatory cytokines (IFN-γ 20 ng/mL + TNF-α 20 ng/mL+ IL-1β 20 ng/mL) for additional 48 h. Apoptosis was measured with cleaved caspase-3 formation via western blot, and by TUNEL assay. C57BL/6J mice (12 weeks old) were subjected to I/R injury by elevating the intraocular pressure to 120 mmHg for 60 min, followed by reperfusion. Peptain-1 or scrambled peptide (0.5 μg) was intravitreally injected immediately after I/R injury and 7 days later. One microliter of PBS was injected as vehicle control, and animals were euthanized on day 14 post-I/R injury. Retinal capillary degeneration was assessed after enzyme digestion followed by periodic acid–Schiff staining. Results Our data showed that peptain-1 entered HRECs and blocked proinflammatory cytokine-mediated apoptosis. Intravitreally administered peptain-1 was distributed throughout the retinal vessels after 4 h. I/R injury caused retinal capillary degeneration. Unlike scrambled peptide, peptain-1 protected capillaries against I/R injury. Additionally, peptain-1 inhibited microglial activation and reduced proinflammatory cytokine levels in the retina following I/R injury. Discussion Our study suggests that peptain-1 could be used as a therapeutic agent to prevent capillary degeneration and neuroinflammation in retinal ischemia.